2021
DOI: 10.3390/jcm10153214
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 Antibodies and Factors Associated with Seropositivity at the University of Salamanca: The DIANCUSAL Study

Abstract: Background: Systematic screening for antibodies against SARS-CoV-2 is a crucial tool for surveillance of the COVID-19 pandemic. The University of Salamanca (USAL) in Spain designed a project called “DIANCUSAL” (Diagnosis of New Coronavirus, COVID-19, in University of Salamanca) to measure antibodies against SARS-CoV-2 among its ~34,000 students and academic staff, as the influence of the university community in the spread of the SARS-CoV-2 pandemic in the city of Salamanca and neighboring towns hosting USAL ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
0
3
1
3
Order By: Relevance
“…Notably, there were no significant differences between students of healthcare and other faculties, although the former was slightly more often positive. These results contrast to some extent with the findings that healthcare students seem to have a high prevalence of previous SARS-CoV-2 contacts [ 14 ]. Indeed, while healthcare workers have a high prevalence of previous infections with SARS-CoV-2 [ 38 ] and a high risk of infection [ 39 , 40 ], undergraduate students probably have reduced contact with patients and access to hospital wards because of the general restrictions in access to healthcare services, thus reducing their risk of infection.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Notably, there were no significant differences between students of healthcare and other faculties, although the former was slightly more often positive. These results contrast to some extent with the findings that healthcare students seem to have a high prevalence of previous SARS-CoV-2 contacts [ 14 ]. Indeed, while healthcare workers have a high prevalence of previous infections with SARS-CoV-2 [ 38 ] and a high risk of infection [ 39 , 40 ], undergraduate students probably have reduced contact with patients and access to hospital wards because of the general restrictions in access to healthcare services, thus reducing their risk of infection.…”
Section: Discussioncontrasting
confidence: 94%
“…Interestingly, students in the second year or above appeared to be more likely to contract a SARS-CoV-2 infection. Indeed, Moro et al reported a higher prevalence of anti-SARS-CoV-2 antibodies in postgraduate students than in undergraduates [ 14 ]. These findings may be due to the possibly wider social network of students in the higher years, together with a propensity of early-year students to adhere more closely to institution rules [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zum SARSCoV2Serostatus von Medizinstudierenden gibt es auch international bislang nur wenige veröffentlichte Daten [6,7]. Mit einem standardisierten OnlineFragebogen (Programm Eva Sys V8.0, 2022; Electronic Paper Evaluationssystem GmbH) wur den soziodemographische Daten der Teilnehmenden sowie mög liche Expositionen gegenüber SARSCoV2 im privaten, universitä ren und ggf.…”
Section: Introductionunclassified
“…Zum SARS-CoV-2-Serostatus von Medizinstudierenden gibt es auch international bislang nur wenige veröffentlichte Daten 6 7 . Ziel der im Jahr 2020 begonnenen Studie war, die Seroprävalenz von Medizinstudierenden in der Anfangsphase der Pandemie zu ermitteln und mögliche Risikofaktoren für SARS-CoV-2-Exposition zu erfassen, um gegebenenfalls zeitnah Konsequenzen hinsichtlich ihrer Schulung zur Umsetzung von Infektionsschutz- und Hygienemaßnahmen ziehen zu können und damit zu einem besseren Schutz der Medizinstudierenden selbst und der von ihnen mitbetreuten Patienten beizutragen.…”
Section: Introductionunclassified